2013
DOI: 10.1002/col.21846
|View full text |Cite
|
Sign up to set email alerts
|

Toward the soft metrology of surface gloss: A review

Abstract: The most straightforward way to assess the glossiness of a surface is by measuring the specular reflectance by use of a specular glossmeter. Although alternative measurement methods have been proposed, this is still the most frequently used instrumental measurement technique for gloss evaluation until today. However, due to both the multidimensional nature of gloss perception and to the initial purpose of a specular glossmeter only to judge the gloss differences of surfaces with similar appearance, specular gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 85 publications
(183 reference statements)
0
45
0
Order By: Relevance
“…The inconsistency between instrumental measurement and visual analysis for the gloss value is not only a widely known fact, but the reason for this inconsistency might be due to the validation method: Leloup et al (2014) attribute this insufficient result to "the fact that specular glossmeter readings were originally only intended to correlate in rank with visual judgements" (Leloup et al 2014). The same could be said about the gloss impression, as in the present study a correspondence between instrumental and sensory data was only found by using ordinal scales.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The inconsistency between instrumental measurement and visual analysis for the gloss value is not only a widely known fact, but the reason for this inconsistency might be due to the validation method: Leloup et al (2014) attribute this insufficient result to "the fact that specular glossmeter readings were originally only intended to correlate in rank with visual judgements" (Leloup et al 2014). The same could be said about the gloss impression, as in the present study a correspondence between instrumental and sensory data was only found by using ordinal scales.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method is highly limited in describing what human can perceive; therefore new approaches are needed to achieve a better correspondence to the human perception (Leloup et al 2014). The limitations of existing methods were noticed in different studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Also, as novel material technology has grown and its application has extended to commercial products to cause complex color perception such as gloss, pearlescence, texture, and goniochromatism, new measurement techniques have been developed to characterize material properties with relevance to the complex color perception. [5][6][7][8] On account of such development of colorimetry and its industrial applications, surface color measurements have been investigated in terms of an uncertainty. An uncertainty in surface color measurements is interpreted as a detection threshold of color difference, .i.e., it is analogous to the color discrimination of human eyes.…”
Section: Introductionmentioning
confidence: 99%